Sudut Pandang Masyarakat terhadap Peranan Tasawuf pada Era Modern di Indonesia - Dhita Fadhilatul Azizah; Naan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the community's point of view on the role of Sufism in the modern era in Indonesia. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the theory of Sufism, while the material object is the reality of modern society. The results and discussion in this study indicate that the community's perspective on the role of the outer and inner Sufism framework is understood as a solution in overcoming the problems of the modern era. This study concludes that Sufism plays a role in overcoming various problems of the modern era from the perspective of the people in the country. This study recommends Islamic religious institutions and organizations to develop the role of Sufism widely and as a solution in overcoming the problems of society in the modern era in Indonesia.